Toll-Like Receptor 2 Is a Regulator of Circadian Active and Inactive State Consolidation in C57BL/6 Mice - DeKorver, Nicholas W.; Chaudoin, Tammy R.; Bonasera, Stephen J. (Frontiers in Aging Neuroscience, 2017)
Regulatory systems required to maintain behavioral arousal remain incompletely understood. We describe a previously unappreciated role that toll-like receptor 2 (Tlr2, a membrane bound pattern recognition receptor that recognizes specific bacterial, viral, and fungal peptides), contributes toward regulation of behavioral arousal. In 4-4.5 month old mice with constitutive loss of Tlr2 function (Tlr2-/- mice), we note a marked consolidation in the circadian pattern of both active and inactive states. Specifically, Tlr2-/- mice demonstrated significantly fewer but longer duration active states during both the circadian dark and light cycles. Tlr2-/- mice also consumed less food and water, and moved less during the circadian light cycle. Analysis of circadian rhythms further suggested that Tlr2-/- mice demonstrated less day-to-day variability in feeding, drinking, and movement behaviors. Reevaluation of this same mouse cohort at age 8-8.5 months revealed a clear blunting of these differences. However, Tlr2-/- mice were still noted to have fewer short-duration active states during the circadian dark cycle, and continued to demonstrate significantly less day-to-day variability in feeding, drinking, and movement behaviors. These results suggest that Tlr2 function may have a role in promoting transitions between active and inactive states. Prior studies have demonstrated that Tlr2 regulates sickness behaviors including hypophagia, hyperthermia, and decreased activity. Our work suggests that Tlr2 function also evokes behavioral fragmentation, another aspect of sickness behavior and a clinically significant problem of older adults.